Borrelia miyamotoi and Borrelia burgdorferi sensu lato widespread in urban areas of the Czech Republic - Alena Balážová; Tomáš Václavík; Vojtech Baláž; Pavel Široký (Parasites & Vectors)
Abstract Background Borrelia miyamotoi and Borrelia burgdorferi sensu lato (s.l.) are important zoonotic agents transmitted by Ixodes ricinus ticks, which are widely distributed across Central Europe. Understanding the spatial distribution of these pathogens’ prevalence will help identify areas with increased infection risk and facilitate the implementation of effective preventive measures. Methods We analysed 12,955 I. ricinus ticks collected from 142 towns in the Czech Republic between 2016 and 2018. The ticks were pooled into 2591 groups of five and tested using duplex quantitative polymerase chain reaction (qPCR) for the presence of B. burgdorferi s.l. and B. miyamotoi. For each location, we estimated the overall prevalence of both agents using the EpiTools Epidemiological Calculator for pooled samples and calculated the minimum infection rate (MIR). To assess the potential risk of infection, we combined data on the abundance of nymphs and females with pathogen prevalence at each sampled site. Using a geographic information system (GIS), we mapped the MIR and infection risk of both Borrelia species across all 142 sampled locations and employed a geostatistical method (ordinary kriging) to predict MIR values and infection risk as continuous surfaces across the entire country. Results We detected B. miyamotoi in 110 localities and B. burgdorferi s.l. in all 142 localities. The estimated prevalence of B. miyamotoi and B. burgdorferi s.l. in the collected ticks was 2.1% (95% confidence interval [CI] 1.8–2.3) and 27.1% (95% CI 26.0–28.3), respectively. For B. miyamotoi, we identified previously unknown, geographically distinct hotspots of MIR up to 8.3%, with MIR slightly higher in females (2.3%) than in males (1.9%) and nymphs (1.8%), though the difference was not statistically significant. In contrast, B. burgdorferi s.l. exhibited ubiquitous presence, with consistently high prevalence nationwide, showing similar MIRs in females (16.2%) and males (16.1%), and slightly lower in nymphs (15.6%). The highest infection risk for B. miyamotoi was 12.4 infected vectors per hour in southeastern Moravia, while the highest risk for B. burgdorferi s.l. reached 78.6 infected vectors per hour in the Bohemian-Moravian Highlands. Conclusions Borrelia miyamotoi is widespread, forming distinct high-prevalence areas in certain regions. Borrelia burgdorferi s.l. demonstrates consistently high prevalence across most of the country, except for a few localized areas such as southwestern Czechia. Both pathogens exhibit natural nidality, forming regions with elevated prevalence and infection risk. Long-term time-series data are needed to confirm the spatio-temporal stability of these hotspots. Graphical Abstract